Shear strength of landfills (2015)
Landfills are engineering structures formed with a specific material, whose shear strength properties can be determined in a similar way, as it is done for a geotechnical material. This paper presents results from an experimental program carried out to obtain the strength parameters for Presidente landfill at Valle del Cauca (Colombia). The experimental program included unconsolidated undrained direct shear tests (UU) performed on laboratory reconstituted samples. Variation of the internal friction angle and cohesion, as a function of the specific weight, depth and decomposition time of the landfill was evaluated. Results were also compared to international values used for design purposes. Results showed a remarkable influence of the waste decomposition time in the shear strength. Some relationship with the depth was also found. Obtained strength parameters are within international ranges recommended for design purposes.